The link between cutaneous inflammation and cognitive impairment. (2nd July 2022) - Wen, S.; Elias, P.M.; Wakefield, J.S.; Mauro, T.M.; Man, M.‐Q.
Abstract: Cognitive impairment is a symptom of neurological disorders, including dementia and Alzheimer's disease; and mild cognitive impairment can be a precursor of both disorders. Aged humans and animal models with other systemic disorders, such as cardiovascular diseases and diabetes, display a higher incidence of cognitive decline. Epidemiological studies have shown that the incidence of cognitive impairment also is higher in subjects with certain inflammatory skin disorders, including psoriasis and chronic eczematous dermatitis. Chronologically aged individuals exhibit increased cutaneous inflammation and elevated circulating cytokine levels, linked to alterations in epidermal function, which itself can induce cutaneous inflammation. Conversely, strategies that improve epidermal function can lower cytokine levels in both the skin and circulation. Thus, it seems likely that epidermal dysfunction could contribute, at least in part, to the development of chronic low‐grade inflammation, also termed 'inflammaging', in the elderly. The evidence of cognitive impairment in patients with inflammatory dermatoses suggests a link between cutaneous inflammation and cognitive impairment. Because of the pathogenic role of epidermal dysfunction in ageing‐associated cutaneous inflammation, improvements in epidermal function could be an alternative approach for mitigation of the ageing‐associated decline in cognitive function.